Built Environment and Active Transport to School (BEATS) Study: protocol for a cross-sectional study. Issue 5 (24th May 2016) - Mandic, Sandra; Williams, John; Moore, Antoni; Hopkins, Debbie; Flaherty, Charlotte; Wilson, Gordon; García Bengoechea, Enrique; Spence, John C
Abstract : Introduction: Active transport to school (ATS) is a convenient way to increase physical activity and undertake an environmentally sustainable travel practice. The Built Environment and Active Transport to School (BEATS) Study examines ATS in adolescents in Dunedin, New Zealand, using ecological models for active transport that account for individual, social, environmental and policy factors. The study objectives are to: (1) understand the reasons behind adolescents and their parents' choice of transport mode to school; (2) examine the interaction between the transport choices, built environment, physical activity and weight status in adolescents; and (3) identify policies that promote or hinder ATS in adolescents. Methods and analysis: The study will use a mixed-method approach incorporating both quantitative (surveys, anthropometry, accelerometers, Geographic Information System (GIS) analysis, mapping) and qualitative methods (focus groups, interviews) to gather data from students, parents, teachers and school principals. The core data will include accelerometer-measured physical activity, anthropometry, GIS measures of the built environment and the use of maps indicating route to school (students)/work (parents) and perceived safe/unsafe areas along the route. To provide comprehensive data for understanding how to change the infrastructure to support ATS, the study will also examine complementary variables such as individual, family and social factors, including student and parental perceptions of walking and cycling to school, parental perceptions of different modes of transport to school, perceptions of the neighbourhood environment, route to school (students)/work (parents), perceptions of driving, use of information communication technology, reasons for choosing a particular school and student and parental physical activity habits, screen time and weight status. The study has achieved a 100% school recruitment rate (12 secondary schools). Ethics and dissemination: The study has been approved by the University of Otago Ethics Committee. The results will be actively disseminated through reports and presentations to stakeholders, symposiums and scientific publications.